Prognostic Significance of Preoperative Systemic Cellular Inflammatory Markers in Gliomas: A Systematic Review and Meta‐Analysis - Wang, Da‐Peng; Kang, Kai; Lin, Qi; Hai, Jian (Clinical and translational science, 2020)
Glioma is the most common malignant brain tumor and has high lethality. This tumor generated a robust inflammatory response that results in the deterioration of the disease. However, the prognostic role of systemic cellular inflammatory indicators in gliomas remains controversial. This meta‐analysis aimed to assess the prognostic significance of preoperative neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), lymphocyte/monocyte ratio (LMR), red cell distribution width (RDW), and prognostic nutritional index (PNI) in patients with gliomas. Databases of PubMed, EMBASE, Web of Science, and The Cochrane Library were systematically searched for all studies published up to January 2019. Study screening and data extraction followed established Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. The Newcastle–Ottawa Scale was used to assess the quality of studies. Eighteen studies containing 3,261 patients were included. The analyses showed an increased NLR or RDW was found to be an independent predictor of worse survival in patients with gliomas (hazard ratio (HR): 1.38; 95% confidence interval (CI): 1.09–1.74; P = 0.008; and HR: 1.40; 95% CI: 1.13–1.74; P = 0.002, respectively). Furthermore, a higher PNI indicates a better overall survival (OS; HR: 0.57; 95% CI: 0.42–0.77; P = 0.0002). For the evaluation of PLR and LMR, none of these variables correlated with OS (P = 0.91 and P = 0.21, respectively). Our meta‐analysis indicates the NLR, RDW, and PNI rather than PLR and LMR are the independent index for predicting the OS of gliomas. Pre‐operative NLR, RDW, and PNI can help to evaluate disease progression, optimize treatment, and follow‐up in patients with gliomas.